PENGARUH LAYANAN BIMBINGAN KELOMPOK TEKNIK SOSIODRAMA PADA KECERDASAN EMOSI SISWA KELAS XI AKUNTANSI KEUANGAN LEMBAGA (AKL) SMK NEGERI 2 SEMARANG: THE INFLUENCE OF SOCIODRAMA TECHNIQUE GROUP GUIDANCE SERVICES ON THE EMOTIONAL INTELLIGENCE OF CLASS XI FINANCIAL ACCOUNTING INSTITUTION (AKL) SMK NEGERI 2 SEMARANG - Lina suryati (Prodi Bimbingan dan Konseling universitas PGRI Semarang, 2025)
This research aims to increase the emotional intelligence of class XI students at SMK N 2 Semarang using the sociodrama technique group guidance services. This type of research is quantitative research with the type of experimental method used, namely pre-experimental design one-group pretest-posttest design. The population in this study was 108 students of class XI AKL (Institutional Financial Accounting) and the sample of this research was students of class sampling. Based on the hypothesis test, a significance (2-tailed) result of 0.000 was obtained. So the results of the significance value (2-tailed) < 0.05 or 0.000 < 0.05. So there is a significant difference between the pretest and posttest. This shows that the guidance of the sociodrama technical group can have an influence on the emotional intelligence of class XI AKL (Institutional Financial Accounting) students at SMK N 2 Semarang.